Comparison of sediment carbon storage between Sungai Tiram Laut and Sungai Sepetang at Matang Mangrove Forest, Perak - Abd Rashid, Noor Hurriyah (2018)
Mangroves are woody plants that grow at the interface between land and sea in tropical and subtropical latitudes where they exist in conditions of high salinity, extreme tides, strong winds, high temperature, and muddy anaerobic soils. The objective of this study was to examine the of sediment properties and compared the sediment carbon storage between Sungai Tiram Laut and Sungai Sepetang at Matang Mangrove Forest, Perak. Selected sediment was defined physical properties (soil texture) and chemical properties (soil pH, soil electrical conductivity, total organic matter, soil organic matter, nitrogen and phosphorus. Data obtained were analyzed using Statistical Analysis System (SAS) version 9.4. The results showed that the sediment was in class sandy loam. Carbon storage of sediment was influenced by many factors, including soil pH and soil electrical conductivity. The total of organic (TOC) in Sungai Sepetang detect too little compared to Sungai Tiram Laut. There element total of organic (TOC) analyzed using a simple and swift method dry combustion method (Loss of ignition method). The finding of the study showed that Sungai Tiram Laut was more efficient in storing carbon. Therefore, it been proved that the carbon stored in mangrove with different amount at different locations. Carbon storage of sediment in the river, because of industrial activities, agriculture, oil palm area and shrimp pool in Sungai Sepetang.